Descemet's Stripping Automated Endothelial Keratoplasty Outcomes Compared with Penetrating Keratoplasty from the Cornea Donor Study - Price, Marianne O.; Gorovoy, Mark; Benetz, Beth A.; Price, Francis W.; Menegay, Harry J.; Debanne, Sara M.; Lass, Jonathan H. (Ophthalmology (Rochester, Minn.), 2010)
To assess outcomes 1 year after Descemet's stripping automated endothelial keratoplasty (DSAEK) in comparison with penetrating keratoplasty (PKP) from the Specular Microscopy Ancillary Study (SMAS) of the Cornea Donor Study. Multicenter, prospective, nonrandomized clinical trial. A total of 173 subjects undergoing DSAEK for a moderate risk condition (principally Fuchs' dystrophy or pseudophakic/aphakic corneal edema) compared with 410 subjects undergoing PKP from the SMAS who had clear grafts with at least 1 postoperative specular image within a 15-month follow-up period. The DSAEK procedures were performed by 2 experienced surgeons per their individual techniques, using the same donor and similar recipient criteria as for the PKP procedures in the SMAS performed by 68 surgeons at 45 sites, with donors provided from 31 eye banks. Graft success and complications for the DSAEK group were assessed and compared with the SMAS group. Endothelial cell density (ECD) was determined from baseline donor, 6-month (range, 5–7 months), and 12-month (range, 9–15 months) postoperative central endothelial images by the same reading center used in the SMAS. Endothelial cell density and graft survival at 1 year. Although the DSAEK recipient group criteria were similar to the PKP group, Fuchs' dystrophy was more prevalent in the DSAEK group (85% vs. 64%) and pseudophakic corneal edema was less prevalent (13% vs. 32%, P<0.001). The regraft rate within 15 months was 2.3% (DSAEK group) and 1.3% (PKP group) ( P = 0.50). Percent endothelial cell loss was 34±22% versus 11±20% (6 months) and 38±22% versus 20±23% (12 months) in the DSAEK and PKP groups, respectively (both P<0.001). Preoperative diagnosis affected endothelial cell loss over time; in the PKP group, the subjects with pseudophakic/aphakic corneal edema experienced significantly higher 12-month cell loss than the subjects with Fuchs' dystrophy (28% vs. 16%, P = 0.01), whereas in the DSAEK group, the 12-month cell loss was comparable for the 2 diagnoses (41% vs. 37%, P = 0.59). One year post-transplantation, overall graft success was comparable for DSAEK and PKP procedures and endothelial cell loss was higher with DSAEK. Proprietary or commercial disclosure may be found after the references.